LONELINESS AMONG OLDER ADULTS IN RURAL INDIA: A SOCIO-DEMOGRAPHIC AND HEALTH PERSPECTIVE - B, Narendra; Sujatha D, Sai (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Loneliness is an emerging public health concern, particularly among older adults in rural settings. It is defined as a distressing subjective experience resulting from deficiencies in social relationships. In India, changing family structures, migration, and socio-economic disparities exacerbate loneliness among the elderly, necessitating targeted research and interventions. This study examines the prevalence of loneliness and its association with demographic, socio-economic, health, and lifestyle factors among older adults in Kurnool district, Andhra Pradesh.